2021
DOI: 10.3389/fonc.2021.705866
|View full text |Cite
|
Sign up to set email alerts
|

The Balance Between the Effectiveness and Safety for Chemotherapy-Induced Nausea and Vomiting of Different Doses of Olanzapine (10 mg Versus 5 mg): A Systematic Review and Meta-Analysis

Abstract: IntroductionThe aim of this study is to rigorously review the efficacy and safety of olanzapine in chemotherapy-induced nausea and vomiting (CINV) settings including (1) at 5- and 10-mg doses, and (2) the setting of highly emetogenic chemotherapy (HEC) and moderately emetogenic chemotherapy (MEC).MethodsEmbase, Pubmed, and Cochrane Library were searched from the establishment of the database through April 18, 2021. The primary efficacy endpoints were the rate of complete response (CR; no emesis and no rescue),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Therefore, we used a 5-mg olanzapine dose in our study. 34 The study was not intended to compare DEX with fosaprepitant. Our objective was to determine whether a three-drug antiemetic regimen without DEX was equally effective when compared with a standard three-drug regimen that included DEX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we used a 5-mg olanzapine dose in our study. 34 The study was not intended to compare DEX with fosaprepitant. Our objective was to determine whether a three-drug antiemetic regimen without DEX was equally effective when compared with a standard three-drug regimen that included DEX.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 35 However, using higher doses of DEX and olanzapine is associated with more adverse events. 4 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 153 patients who received cisplatin were enrolled in a phase II clinical study conducted by Takako; the results showed that the CR for delayed period was 78% (80% CI: 70.3–83.8, p = 0.01) in the 10 mg olanzapine group and 86% (80% CI: 79.2–90.7, p < 0.001) in the 5 mg olanzapine group; incidence of somnolence was 53.3% and 45.5%, respectively [ 33 ]. This also suggests that both 10 mg and 5 mg of olanzapine significantly improved delayed vomiting, dramatically reduced the frequency and duration of nausea in high-risk patients, and 5 mg olanzapine causes less somnolence [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Antiemetic Effects Of Olanzapine In Different Dosesmentioning
confidence: 98%
“…This suggests that olanzapine is more effective than metoclopramide in controlling breakthrough CINV among patients with HEC, and it may become an effective antiemetic drug for breakthrough CINV [ 25 ]. In addition, no grade 3 or 4 toxicity was observed in phase III trials of olanzapine at 5–10 mg, before and 3–4 days after chemotherapy [ 26 , 27 , 28 , 29 ]. Specifically, there was no significant dizziness, drowsiness, extrapyramidal reactions, or cathisophobia.…”
Section: Safety Of Olanzapine In the Prevention And Treatment Of Cinvmentioning
confidence: 99%
“…Recent studies have suggested that, when compared to a 10mg dose, a 5mg dose of olanzapine resulted in similar control of CINV and oftentimes was associated with less sedation. [11][12][13][14]…”
Section: Atypical Antipsychotics (Olanzapine)mentioning
confidence: 99%